2018
DOI: 10.1007/s12195-018-0538-7
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanosensitive Ion Channel TRPV4 is a Regulator of Lung Development and Pulmonary Vasculature Stabilization

Abstract: Introduction – Clinical observations and animal models suggest a critical role for the dynamic regulation of transmural pressure and peristaltic airway smooth muscle contractions for proper lung development. However, it is currently unclear how such mechanical signals are transduced into molecular and transcriptional changes at the cell level. To connect these physical findings to a mechanotransduction mechanism, we identified a known mechanosensor, TRPV4, as a component of this pathway. Methods – Embryonic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 65 publications
0
23
0
1
Order By: Relevance
“…Thus, TRPV4 might become a therapeutic target in hypertension treatment. Additionally, TRPV4 is involved in converting mechanical forces on the airways to molecular and transcriptional events, regulating the development of lung and stabilization of pulmonary vasculature ( Morgan et al, 2018 ). Recent evidence suggests that activating pulmonary capillary endothelial TRPV4 channels enhance pulmonary venous pressure-induced edema and TRPV4 blockade prevents the increased vascular permeability and pulmonary edema ( Thorneloe et al, 2012 ), highlighting a pharmacological therapeutic potential of TRPV4 inhibition for pulmonary edema induced by heart failure.…”
Section: Transient Receptor Potential Vanilloid 4 As a Potential Thermentioning
confidence: 99%
“…Thus, TRPV4 might become a therapeutic target in hypertension treatment. Additionally, TRPV4 is involved in converting mechanical forces on the airways to molecular and transcriptional events, regulating the development of lung and stabilization of pulmonary vasculature ( Morgan et al, 2018 ). Recent evidence suggests that activating pulmonary capillary endothelial TRPV4 channels enhance pulmonary venous pressure-induced edema and TRPV4 blockade prevents the increased vascular permeability and pulmonary edema ( Thorneloe et al, 2012 ), highlighting a pharmacological therapeutic potential of TRPV4 inhibition for pulmonary edema induced by heart failure.…”
Section: Transient Receptor Potential Vanilloid 4 As a Potential Thermentioning
confidence: 99%
“…While these platforms are highly complex and challenging to develop, there is a corresponding increase in control and ability to separate spatiotemporal responses, with less sacrifice of physiologic conditions. These models are common for studying organ development 91 , 165 , 168 , 200 and bioreactors for organ and lung conditioning for transplant, 96 , 188 but less common with applications to studying disease pathophysiology. This is especially critical in studying SARS-CoV-2 pathology and the progression of COVID-19.…”
Section: Opportunities For Bioengineers To Study Respiratory Viral LImentioning
confidence: 99%
“…In branching morphogenesis occurring in the lung, kidney, vascular system, prostate, mammary gland, and kidney to form tubular branching structures, a leader or "tip" cell responds to a chemotactic or durotactic gradient and protrudes while bringing along follower or "stalk" cells through adhesion junctions. Several studies have shown that mechanically sensitive molecules such as YAP (43), integrin 1 (44), and the TRPV4 ion channel (45), are needed for proper branching morphogenesis, yet measurement of cell-cell force during this process in vivo is limited. Since in vivo collective cell migration is di cult to quantify, especially with respect to cell-cell and cell-matrix forces, our model provides a method for understanding this fundamental aspect of development and disease.…”
Section: Physiological Significancementioning
confidence: 99%